(untitled) (Sebha University Conference Proceedings, 2024)
In the present study, Ni-P composite coating layer has been produced under direct plating condition. The voltage during the experiments has been measured, the results showed that voltage increases with increasing the experiment time. The average applied currents were 0.05 A, 0.08 A and 0.12 A. The employed current densities led to Ni-P rich deposition in all experiments but the average coating thickness was increases with increasing the applied current density. The increasing of electroplating path temperature can also causes increasing in the thickness of Ni-P deposition layer. The best obtained hardness result was at current density of 0.08 A as 285.7 HV. The low alloy steel samples coated by Ni-P deposition layer were heat treated at 400 °C for 1hr causing increasing in microhardness from 270 to about 443.8 HV. XRD analysis showed that Ni-P deposits with 8wt.% are considered as amorphous phase and after heat treatment it was crystallized at steady phases of Ni and Ni₃P deposits.